Improving the Quality of Corn Cob Compost Fertilizer with Various Raw Material Compositions - Ugik Romadi; Selly Ika Damayanti; Rika Despita (Universitas Bangka Belitung, 2026)
Farmers have not yet utilized corn cobs, one of the agricultural wastes. Corn cobs themselves contain organic material, which can be optimized as an ingredient for making organic fertilizer. However, the habit of farmers when the harvest season arrives is that they burn or pile up corn cobs on their agricultural land. This results in the accumulation of corn cob waste increasing every time the harvest season takes place. Methods to determine the best composition of corn cob compost by testing its effectiveness using various formulations. The research was conducted using a Completely Randomized Design (CRD) with 4 treatments and 6 replications. P1 pure composition of corn cobs, P2 (2:1) corn cobs and cow cohe, P3 (1:2) corn cobs and cow cohe, P4 (1:1) corn cobs and cow cohe. Results In this research, the parameters observed include pH, temperature, macronutrients (N, P, K), C-organic, C/N ratio, color, odor/aroma, and texture. pH and temperature checks are carried out every 3 days in the morning. Laboratory tests are carried out to determine the content of macronutrients (N, P, K), C-organic, and the C/N ratio. Meanwhile, organoleptic tests were carried out on texture and aroma parameters by 3 expert panelists. Conclusion: Based on the results of observations and laboratory tests, the best composition of corn cob compost fertilizer is found in P2 with a composition of cow cobs and kohe (2:1).